Reorientação do olhar: uma aventura científica - Adametes, Claudia Megale (Faculdade de Ciências e Letras - Unesp - Araraquara., 2017)
This article to concern about das discusses metodológicas e epistomológicas what include the approach and the research's object in Social Science and it proposes, it's based with ideas of contemporaries authors from Social Theory, it doesn't only a sight's dislocation with regard to the research place, but a reorganization of the text from this sight with a kind of reasonable what to want to be only, predominate, global.